Floristic diversity of Naungan mangrove ecosystem in Ormoc, the largest port city in Leyte, Philippines - ARTURO E. PASA; VAL JASON D. SOLANO; SHAINA MAE S. FIGUEROA; ERNIE O. VALENZONA; ANNE FRANCES V. BUHAY; INOCENCIO E. BUOT JR (Society for Indonesian Biodiversity, 2024)
Abstract. Pasa AE, Solano VJD, Figueroa SMS, Valenzona EO, Buhay AFV, Buot Jr IE. 2024. Floristic diversity of Naungan mangrove ecosystem in Ormoc, the largest port city in Leyte, Philippines. Biodiversitas 25: 2093-2103. Assessing the floristic diversity of the Naungan mangrove ecosystem in Ormoc, the largest port city in Leyte and a highly susceptible area to geologic and natural hazards, extreme weather events and human disturbances, is vital to determine available resources and ecosystem services for communities. This study aimed to evaluate the present state of the mangrove ecosystem in Naungan by analyzing its floristic diversity, composition, and structural characteristics. A total of 55 nested quadrats were established as observation points, measuring 10 m x 10 m and 5 m x 5 m to document the upper canopy and understorey vegetation, respectively. Mangroves with a diameter of 10 cm and above were recorded for the upper canopy while plants with diameter below 10 cm were recorded for the understorey. Results showed that the upper canopy vegetation has a total of 331 individuals of which are 10 tree species belonging to 8 families while the understorey canopy has a total of 1,310 individuals of which are 23 species belonging to 15 families. The diversity of upper canopy vegetation, as measured by the Shannon index, is notably low at 1.492. Similarly, the understorey diversity, with a value of 2.198, falls into the low category. When considering the combined diversity of both upper and lower canopies, the overall score remains low at 2.176. Avicennia marina is the most dominant upperstorey species with a relative abundance of 0.39275 followed by Sonneratia alba with 0.27492 and Avicennia officinalis with 0.16012. The understorey is also dominated by Avicennia marina with a relative abundance of 0.352672 followed by Nypa fruticans with 0.118321 and Rhizophora apiculata with 0.10229. Aegiceras floridum and Ceriops decandra are “nearly threatened” while the other species are under the “least concern” category. The area is managed by a people’s organization but threats such as fishpond establishment, road construction, and subsistence farming remain and are expected to affect mangrove diversity and ecosystem services. A mangrove ecosystem conservation framework is proposed, incorporating the importance of policy intervention and local participation in realizing sustainable mangrove ecosystems and stable provisions of the ecosystem services.